Dynamic Changes in Binding of Immunoglobulin Heavy Chain 3′ Regulatory Region to Protein Factors during Class Switching - Chatterjee, Sanjukta (American Society for Biochemistry and Molecular Biology, 2011)
The 3′ regulatory region (3′ RR) of the Igh locus works at long distances on variable region (V(H)) and switch region (I) region promoters to initiate germ line (non-coding) transcription (GT) and promote class switch recombination (CSR). The 3′ RR contains multiple elements, including enhancers (hs3a, hs1.2, hs3b, and hs4) and a proposed insulator region containing CTCF (CCCTC-binding factor) binding sites, i.e. hs5/6/7 and the downstream region (“38”). Notably, deletion of each individual enhancer (hs3a-hs4) has no significant phenotypic consequence, suggesting that the 3′ RR has considerable structural flexibility in its function. To better understand how the 3′ RR functions, we identified transcription factor binding sites and used chromatin immunoprecipitation (ChIP) assays to monitor their occupancy in splenic B cells that initiate GT and undergo CSR (LPS±IL4), are deficient in GT and CSR (p50(−/−)), or do not undergo CSR despite efficient GT (anti-IgM+IL4). Like 3′ RR enhancers, hs5–7 and the 38 region were observed to contain multiple Pax5 binding sites (in addition to multiple CTCF sites). We found that the Pax5 binding profile to the 3′ RR dynamically changed during CSR independent of the specific isotype to which switching was induced, and binding focused on hs1.2, hs4, and hs7. CTCF-associated and CTCF-independent cohesin interactions were also identified. Our observations are consistent with a scaffold model in which a platform of active protein complexes capable of facilitating GT and CSR can be formed by varying constellations of 3′ RR elements.